The Metacaspase TaMCA-Id Negatively Regulates Salt-Induced Programmed Cell Death and Functionally Links With Autophagy in Wheat - Yue, Jie-yu; Wang, Ying-jie; Jiao, Jin-lan; Wang, Wen-wen; Wang, Hua-zhong (Frontiers in Plant Science, 2022)
Metacaspases (MCAs), a family of caspase-like proteins, are important regulators of programmed cell death (PCD) in plant defense response. Autophagy is an important regulator of PCD. This study explored the underlying mechanism of the interaction among PCD, MCAs and autophagy, and their impact on wheat response to salt stress. In the current study, the wheat salt-responsive gene TaMCA-Ⅰd was identified. The open reading frame (ORF) of TaMCA-Ⅰd was 1071 bp, coding 356 amino acids. The predicted molecular weight and isoelectric point were 38,337.03 Da and 8.45, respectively. TaMCA-Ⅰd had classic characteristics of type I MCAs domains, a typical N-terminal pro-domain rich in proline. TaMCA-Ⅰd was mainly localized in the chloroplast, and exhibited nucleocytoplasmictrafﬁcking under NaCl treatment. Increased expression of TaMCA-Ⅰd in wheat seedling roots and leaves was triggered by 150 mM NaCl treatment. Silencing of TaMCA-Ⅰd enhanced sensitivity of wheat seedlings to NaCl stress. Under NaCl stress, TaMCA-Ⅰd-silenced seedlings exhibited a reduction in activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT), higher accumulation of H2O2 and O2.−, more serious injury to photosystem II (PSII), increase of PCD level and autophagy activity in leaves of wheat seedlings. These results indicated that TaMCA-Ⅰd functioned in PCD through interacting with autophagy under NaCl stress, which could be used to improve salt tolerance of crop plant.